Computational models predict larger muscle tissue strains at faster sprinting speeds - Fiorentino, N. M.; Rehorn, M. R.; Chumanov, E. S.; Thelen, D. G.; Blemker, S. S. (Medicine & Science in Sports & Exercise, 2014)
Introduction: Proximal biceps femoris musculotendon strain injury has been well established as a common injury among athletes participating in sports that require sprinting near or at maximum speed; however, little is known about the mechanisms that make this muscle tissue more susceptible to injury at faster speeds. Purpose: This study aimed to quantify localized tissue strain during sprinting at a range of speeds. Methods: Biceps femoris long head (BFlh) musculotendon dimensions of 14 athletes were measured on magnetic resonance (MR) images and used to generate a finite-element computational model. The model was first validated through comparison with previous dynamic MR experiments. After validation, muscle activation and muscle-tendon unit length change were derived from forward dynamic simulations of sprinting at 70%, 85%, and 100% maximum speed and used as input to the computational model simulations. Simulations ran from midswing to foot contact. Results: The model predictions of local muscle tissue strain magnitude compared favorably with in vivo tissue strain measurements determined from dynamic MR experiments of the BFlh. For simulations of sprinting, local fiber strain was nonuniform at all speeds, with the highest muscle tissue strain where injury is often observed (proximal myotendinous junction). At faster sprinting speeds, increases were observed in fiber strain nonuniformity and peak local fiber strain (0.56, 0.67, and 0.72 for sprinting at 70%, 85%, and 100% maximum speed). A histogram of local fiber strains showed that more of the BFlh reached larger local fiber strains at faster speeds. Conclusions: At faster sprinting speeds, peak local fiber strain, fiber strain nonuniformity, and the amount of muscle undergoing larger strains are predicted to increase, likely contributing to the BFlh muscle`s higher injury susceptibility at faster speeds.